Microenvironments Enabled by Covalent Organic Framework Linkages for Modulating Active Metal Species in Photocatalytic CO2 Reduction. (15th January 2022) - Yang, Shuailong; Sa, Rongjian; Zhong, Hong; Lv, Haowei; Yuan, Daqiang; Wang, Ruihu
Abstract: Covalent organic frameworks (COFs) are promising platforms for understanding photocatalytic CO2 reduction processes owing to their predesignable structures and tailor‐made functions. Herein, a nickel‐modified COF composed of N ‐acylhydrazone‐linked electron‐donor and electron‐acceptor dyads (H‐COF‐Ni) is reported. H‐COF‐Ni generates 5694 µ mol g −1 of CO with 96% selectivity over H2 evolution in 2 h under visible light irradiation, which greatly outperforms that of typical imine‐linked counterpart. Experimental and theoretical results have demonstrated that metal active sites in host frameworks are deprived by 2, 2′‐bipyridine additive to form new catalytic active species, the separation and transfer process of the photogenerated charge carriers are not main reason for their activity difference. The linkage‐dependent activation of CO2 molecules on Ni centers is responsible for high photocatalytic efficiency. This study provides new protocols to improve CO2 photoreduction performance through the modification of linkage microenvironments. Abstract : A covalent organic framework containing N ‐acylhydrazone linkage is presented. The N ‐acylhydrazone can chelate with Ni ions, but the presence of 2, 2′‐bipyridine (bpy) generates Ni‐bpy adduct as active species for photocatalytic CO2 reduction. It is proposed that photocatalytic activity is closely related with CO2 activation, not separation and transfer of the photogenerated electron when compared with the imine‐linked counterpart.